The stories of women, by women, married to male ministry leaders - Jones, Lisa (Mental health, religion & culture, 2021)
This qualitative research study captured the narratives of women married to men in ministry leadership roles. Although much empirical research has been published on the effects of stress on men and women in full-time ministry, few studies have explored personal narratives of the ministry wife or the effects on her family. The purpose of this qualitative study was to explore the satisfaction, expectations, fears, regrets, and insights of the fishbowl life through exploring wives’ narratives. Twenty-six ministers’ wives volunteered to participate using a confidential, semi-structured interview of seven open-ended questions. The three primary themes that emerged through the transparency of their stories were (I) shared fears, (II) strain and satisfaction, and (III) (dis)connection in the role of minister's wife. Implications of these findings are discussed to illuminate opportunities for enhanced support and intervention for women married to men in ministerial leadership.